Anti-IL-8 antibody activates myeloid cells and potentiates the anti-tumor activity of anti-PD-1 antibody in the humanized pancreatic cancer murine model. (28th July 2022) - Li, Pan; Rozich, Noah; Wang, Jianxin; Wang, Junke; Xu, Yao; Herbst, Brian; Yu, Raymond; Muth, Stephen; Niu, Nan; Li, Keyu; Funes, Vanessa; Gai, Jessica; et al.
Abstract: Pancreatic ductal adenocarcinoma(PDAC) does not respond to single-agent immune checkpoint inhibitor therapy, including anti-PD-1 antibody(aPD-1) therapy. Higher plasma levels of IL-8 are associated with poorer outcomes in patients who receive aPD-1 therapies, providing a rationale for combination immunotherapy with an anti-IL-8 antibody(aIL-8) and aPD-1. We thus investigated whether human aIL-8 therapy can potentiate the antitumor activity of aPD-1 and further investigated how the combination affects the immune response by regulating myeloid cells in the tumor microenvironment in a humanized murine model of PDAC with a reconstituted immune system consisting of human T cells and a combination of CD14 + and CD16 + myeloid cells. The results show that the combination of aIL-8 and aPD-1 treatment significantly enhanced antitumor activity following the infusion of myeloid cells. Our results further showed that the target of IL-8 is mainly present in CD16 + myeloid cells and is likely to be granulocytes. FACS analysis showed that aIL-8 treatment increased granulocytic myeloid cells in tumors. Consistently, single-nuclear RNA-sequencing analysis of tumor tissue showed that the innate immune response and cytokine response pathways in the myeloid cell cluster were activated by aIL-8 treatment. This is the first preclinical study using a humanized mouse model for new combination immunotherapeutic development and supports the further clinical testing of aIL-8 in combination with aPD-1 for PDAC treatment. This study also suggests that peripherally derived myeloid cells can potentiate the antitumor response of T cells, likely through the innate immune response, and aIL-8 re-educates tumor-infiltrating myeloid cells by activating the innate immune response. Highlights: This is the first preclinical study of anti-IL-8 therapeutic antibodies in a humanized mouse model of pancreatic cancer. This study suggested that anti-IL-8 antibodies potentiate PD-1 blockade and informed the design of an ongoing clinical trial. Anti-IL-8 antibody re-educates tumor-infiltrating myeloid cells by activating innate immune response as a novel mechanism.